SERAPAN FOSFOR DAN PRODUKTIVITAS JAGUNG HIBRIDA PADA PEMBERIAN BIOCHAR SEKAM PADI DI TANAH ULTISOL - Jaya, Ya’ Subahan; Sasli, Iwan; Ramadhan, Tris Haris (Fakultas Pertanian, Universitas Janabadra, 2024)
Rice husk biochar applied to ultisol soil can increase soil fertility physically and chemically. The research aims to determine the role of rice husk biochar in increasing plant phosphorus uptake and its implications for hybrid corn productivity in ultisol soil. The research was conducted in Singkawang City, West Kalimantan, from July to November 2023. The research method was prepared using a one-factor randomized block design, namely without rice husk biochar, application of 6 tons ha-1 of rice husk biochar, and 10 tons ha-1 of rice husk biochar application. Each treatment was repeated 9 times. The results showed that the use of various doses of rice husk biochar on hybrid corn plants played a role in influencing the plant's ability to absorb phosphorus nutrients, increasing plant dry weight and root volume, with the best dose being 10 tons ha-1, but for variable plant yields the use of various doses Rice husk biochar obtained the same results.